The Policy Implementation in Development Water Front City in District Senapelan Pekanbaru - Panca Setyo Prihatin; Kasmanto Rinaldi (Jurnal Studi Pemerintahan, 2013)
Structuring urban areas, especially the Pekanbaru City, is necessary given the problem of development of Pekanbaru City is more and more complex and highly in need of a better arrangement, especially concerning on the improvement of the environment (Water Front City) in Siak River surroundings. This is a descriptive qualitative research with population sample of the Office of Settlement and Regional Infrastructure of Pekanbaru City, Senapelan District Government, NGOs, community leaders, and private parties. Data are collected through interview, observation and documentation, which is then analyzed using qualitative analysis technique. This research finds that the policy of the development of Water Front City at Village Kampung Baru sub-district Senapelan Pekanbaru is not implemented optimally. This situation can be seen through a variety of indicators related to the implementation of development policies of Water Front City at Village Kampung Baru subdistrict Senapelan Pekanbaru in that the effect of interest policies, benefits, desire for change, the process of decision-making, implementing programs and supporting resources have not been implemented effectively. The curbing factors in implementing development policies in the District Water Front City Senapelan Pekanbaru are mostly due to the lack of human resources, process of compensation and other inadequate financing, and managerial instruments that are unsupported to the implementation of development programs of Water Front City at Village Kampung Baru sub-district Senapelan Pekanbaru.